Air‐Stable Monolayer Cu2Se Exhibits a Purely Thermal Structural Phase Transition. Issue 19 (2nd April 2020) - Qian, Kai; Gao, Lei; Chen, Xiya; Li, Hang; Zhang, Shuai; Zhang, Xian‐Li; Zhu, Shiyu; Yan, Jiahao; Bao, Deliang; Cao, Lu; Shi, Jin‐An; Lu, Jianchen; et al.
Abstract: Materials possessing structural phase transformations exhibit a rich set of physical and chemical properties that can be used for a variety of applications. In 2D materials, structural transformations have so far been induced by strain, lasers, electron injection, electron/ion beams, thermal loss of stoichiometry, and chemical treatments or by a combination of such approaches and annealing. However, stoichiometry‐preserving, purely thermal, reversible phase transitions, which are fundamental in physics and can be easily induced, have not been observed. Here, the fabrication of monolayer Cu2 Se, a new 2D material is reported, demonstrating the existence of a purely thermal structural phase transition. Scanning tunneling microscopy, scanning transmission electron microscopy, and density functional theory (DFT) identify two structural phases at 78 and 300 K. DFT calculations trace the phase‐transition mechanism via the existence/absence of imaginary (unstable) phonon modes at low and high temperatures. In situ, variable‐temperature low‐energy electron diffraction patterns demonstrate that the phase transition occurs across the whole sample at ≈147 K. Angle‐resolved photoemission spectra and DFT calculations show that a degeneracy at the Γ point of the energy bands of the high‐temperature phase is lifted in the low‐temperature phase. This work opens up possibilities for studying such phase transitions in 2D materials. Abstract : Purely thermal, stoichiometry‐preserving, structural phase transitions are common in bulk materials, but have not been observed in 2D materials. The fabrication of monolayer Cu2 Se, a new air‐stable 2D material, is reported, demonstrating the existence of purely thermal, stoichiometry‐preserving, reversible phase transitions with a critical temperature of ≈147 K.